Strategi Guru Mata Pelajaran Akidah Akhlak dalam Menanamkan Nilai Karakter Kejujuran dan Disiplin Siswa di MAN 2 Kota Bengkulu - Ani Lestari (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This study Purpose to: (1) Find out the strategy of the Akidah Akhlak subject teacher in instilling the character values of honesty and discipline in students at State Aliyah Madrasah2 Bengkulu City. (2) Knowing the character values of honesty and discipline of State Aliyah Madrasah 2 Bengkulu City students. (3) Knowing the factors that influence the process of naming the character values of honesty and discipline in State Aliyah Madrasah 2 Bengkulu City Students. This type of research is a qualita- tive research with a descriptive approach. The research location is Madrasah Aliyah Negeri (MAN) 2 Bengkulu City. There are two kinds of data collection in this study, namely primary data, which includes: Principals, teachers of Akidah Akhlak subjects and students of class X Mathematics and Natural Sciences. Secondary Data includes: Documents, photos, Administration Staff. The data collection techniques used are observation, interviews and documentation. While the technical analysis of the data used (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of this research are that: (1) The strategy of the teacher of moral aqidah in instilling character education in students by providing examples, spontaneous activities, rep- rimands, environmental conditioning, routine activities of good role models. (2) Student’s condition. In general, it can be said that it is good for students to carry out activities that have been determined by school regulations, arrive on time, pray dhuha in congregation, throw garbage in its place, say good and polite. The whole thing has been done well. However, there are some students who still show attitudes that are not in accordance with their wishes and expectations, such as still not caring, not being responsible for their own actions and tasks. (3) Factors influencing the process of inculcating the character values of honesty and discipline in students (a) Lack of motivation and support from both parents (b) Lack of awareness of students (c). Community environmental factors. The three environments provide examples for students to interact in their daily lives.